Asymmetric surface texturing for directional friction control under dry sliding condition. (March 2023) - Tewelde, Fitsum B.; Zhou, Tianfeng; Zhou, Jia; Guo, Weijia; Zhao, Bin; Ge, Xiangyu; Wang, Wenzhong; Wang, Xiaoli; Wang, Xibin
Abstract: This study investigated the effects of asymmetric surface texturing on directional friction under dry condition. Asymmetric micro-grooves were radially textured on electroless nickel phosphorous (Ni–P) plated disk using a single-point diamond cutting process. Using a ball-on-disk tribometer, sliding tests in clockwise (CW) and counter-clockwise (CCW) directions against polyether-ether-ketones (PEEK) material were carried out at different texture densities. Results show that asymmetric surface texturing has a strong effect on directional friction. At a texture density of 70 %, the friction coefficient in the CW direction increased by 28.1 % compared to the CCW direction. The greatest increase in friction coefficient, 61.3 %, was observed during CW rotation at the lowest texture density compared to the reference untextured surface.